Care demands-related concerns and perceived service needs of families of people with mental illness in the community - Pawi, S.; Chan, K.G; Ong, M.F (Malaysian Psychiatric Association, 2014)
Owing to reduced inpatient stays, people with mental illness were often discharged from the hospital in ‘acute’ conditions. During this transition period of fragility, the relocation of care from hospital to home has tremendous impact on every aspect of a family’s life as they need to face a challenging task of caring especially when they are ‘not ready’ and ‘ignorant’ about the chronicity and severity of the illness. Furthermore, where economic and psychological support is concerned, those who are undertaking this task may require significant professional guidance.